The Uses and evaluation of water resources in the Zalm river basin - Tahseen Abdulrahim Azeez; Mohmeed Hamasalh Sharazory (Zanco Journal of Humanity Sciences)
This study deals with the subject of a geographical assessment of the use of water resources in the Zalam River Basin. The aim of this study is to highlight the reality of the current uses of water resources for various purposes in the study area. And to achieve a balance between the volume of incoming, surface and underground water in the study area, and to find the amount of consumption of water by the population in the various activities.